GENDER INJUSTICE AGAINST WOMEN IN NOVEL MOXIE BY JENNIFER MATHIEU - Nurjana, Nurjana Kuada; Olga A. Rorintulus; Agustine C. Mamentu (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
This research was conducted to describe gender injustice towards women as depicted by female students, male students and school regulations in the novel Moxie by Jennifer Mathieu. This research used a qualitative research where instead of using numbers, the data collected is in the form of words and quotations. In conducting this research, data was taken from the novel by Jennifer Mathieu entitled Moxie as a primary source and was also supported by other relevant references such as journal documents and web sources about gender injustice towards women which were considered secondary sources. In conducting data analysis, researchers used a feminist approach. From this research it can be concluded that there are three acts of injustice experienced by women in the novel Moxie. Acts of gender injustice are marginalization, stereotypes and violence against women.